El gerente y la cultura de las empresas en el Paraguay - García de Benavides, Consuelo (1992)
It gives an approach about management, its styles and the culture of Latin American companies – topics dealt with sparsely and marginally – from Paraguay’s case which country is unique to the rest of the continent. The basic hypothesis is that the social system significantly influences the companies and those who work in it, shaping a style of management and culture typical of those companies and with which their identity is formed. The research, exploratory, was conducted based on three observation elements: in-depth interview, opinion interview and Paraguayan history. It was possible to prove the validity of the theoretical model developed and it was found that the culture of the company is the result of social, economic, political and cultural development and the predominant archetypal dynamics in society and not the simple statement of values and beliefs divorced from the conditions that create the forms of organization. Paraguayan companies were also found to be characterized by traditional management styles and paternalism; their managers believe that managing means applying classic management models, which prevents them from generating their own models that take advantage of the potentials of society and culture.